Neophyte experiences of football (soccer) match analysis: a multiple case study approach - McKenna, M.; Cowan, D. T.; Stevenson, D.; Baker, J. S. (Research in Sports Medicine, 2018)
Performance analysis is extensively used in sport, but its pedagogical application is little understood. Given its expanding role across football, this study explored the experiences of neophyte performance analysts. Experiences of six analysis interns, across three professional football clubs, were investigated as multiple cases of new match analysis. Each intern was interviewed after their first season, with archival data providing background information. Four themes emerged from qualitative analysis: (1) "building of relationships" was important, along with trust and role clarity; (2) "establishing an analysis system" was difficult due to tacit coach knowledge, but analysis was established; (3) the quality of the "feedback process" hinged on coaching styles, with balance of feedback and athlete engagement considered essential; (4) "establishing effect" was complex with no statistical effects reported; yet enhanced relationships, role clarity, and improved performances were reported. Other emic accounts are required to further understand occupational culture within performance analysis.